Compositional Changes during Muskmelon Fruit Ripening (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to investigate compositionalchanges during ripening of three Galia F1 muskmelon cultivars for export;namely, ‘Galeb’, ‘Seeren’ and ‘Green Star’ at 18±1ºC and 85%-90%relative humidity. The fruits of the three cultivars exhibited a typicalclimacteric pattern of respiration during ripening. Fruit flesh firmness wasdeclined progressively in a similar manner in the three cultivars. Rindcolour, total soluble solids (TSS) and weight loss steadily increased andcellulose content decreased with fruit ripening. Total protein increased upto the climacteric peak of respiration and then decreased.